Karakteristik Mutu Selai Lembaran Pedada (Sonneratia caseoloris) dengan Variasi Konsentrasi Agar-agar dan Karagenan sebagai Texturizer - Andari, Mayang; Arif, Hilda Meisya; Azhari, Diah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Sheet jam is a modification of semi-solid jam products into sheets that are dense, practical and not too sticky. This research aims to characterize the effect of adding jelly or carrageenan on the physical, chemical and organoleptic properties of pedada fruit sheet jam. This research consisted of 2 treatments, namely the type of texturizer (jelly and carrageenan) and the concentration of the texturizer (1.5%, 2.25%, 3.0%). Analysis of yield, physical (texture), chemical (water content, fiber, protein, vitamin C, total dissolved solids), organoleptic tests (color, aroma, texture, taste, stickiness and overall), determining the best treatment as well as income and profit analysis are carried out on all sheet jam samples. Analysis of the best treatment using the De Garmo method states that the best sheet jam is found in the treatment with the addition of 1.5% carrageenan concentration, with a yield value of 56.31%, texture 2.32 mm, water content 26.08%, fiber content 0.82%, protein content 5.35%, vitamin C content 0.36% and total dissolved solids 29.70%. Organoleptic tests on color, aroma, texture, taste, stickiness and overall showed values of 4.20%, 3.85%, 3.85%, 3.85%, 3.70% and 4.25%. The results of the income and profit analysis of sheet jam for the best treatment show that with a total cost of Rp. 2,462,907 can generate income of Rp. 3,210,000 with a profit in one month of production of Rp. 747,093Â